Short Notes in Periodontics: A Handbook - Ravishankar, PL (Jaypee Brothers Medical Publishers, 2013)
The book covers all important topics on periodontics and associated diseases with its diagnosis and managements. It also covers different surgical methods used in the management of periodontal diseases like surgical therapy and non surgical therapy with the instruments and materials used during the surgery. Some important topics that are covered in the book are normal periodontium (gingiva, keratinocytes, gingival sulcus), classification and epidemiology of periodontal diseases (chronic periodontitis, aggressive periodontitis, plaque index), etiology of periodontal diseases (dental plaque, calculus, smoking and the periodontium), periodontal pathology (gingival bleeding, gingival recession, periodontal cyst) and diagnosis, prognosis and treatment plan (radiographs, night guards, halimeter). Oral Implantology and supportive periodontal therapy (SPT) are also covered.